2015
DOI: 10.1002/gps.4386
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lifestyle‐related disease on conversion and reversion in patients with mild cognitive impairment: after 12 months of follow‐up

Abstract: The absence of lipid abnormality at baseline may contribute to reversion in patients with MCI. The presence of multiple LSRD was associated with cognitive decline. Our results highlight the contribution of multiple LSRD on increasing conversion and decreasing reversion in patients with MCI. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…One pathway by which physical activity impacts the brain is via the prevention or better management of cardiovascular risk factors (e.g., diabetes, hypertension, hyperlipidemia, and obesity). In fact, among those with MCI, presence of cardiovascular risk factors is associated with increased likelihood of progression to dementia [38]. Cardiovascular risk factors are associated with various changes to brain health.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…One pathway by which physical activity impacts the brain is via the prevention or better management of cardiovascular risk factors (e.g., diabetes, hypertension, hyperlipidemia, and obesity). In fact, among those with MCI, presence of cardiovascular risk factors is associated with increased likelihood of progression to dementia [38]. Cardiovascular risk factors are associated with various changes to brain health.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Previous community-based studies also reported the predictors of MCI progression, e.g., older age, shorter years of school, depression, with history of diabetes or stroke, African Americans and Hispanic, and baseline MMSE score [8] , [11] , [12] , [13] , [14] , [22] , [23] , [24] . Other predictors were reported mostly from hospital-based studies, such as female gender [25] , APOE genotype [26] , white matter hyperintensities [27] , lifestyle-related disease (hypertension, type II diabetes mellitus, and lipid abnormality) [28] , high plasma C-reactive protein level [29] , orthostatic blood pressure behavior [30] , and unstable body mass index [31] . Our study explored the older age, APOE ε4 allele positive and low MMSE score at baseline, but not the gender and education years, were the independent risk predictors to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous community-based studies also reported the predictors of MCI progression, e.g., older age, shorter years of school, depression, with history of diabetes or stroke, African Americans and Hispanic, and baseline MMSE score [8,[11][12][13][14][22][23][24]. Other predictors were reported mostly from hospital-based studies, such as female gender [25], APOE genotype [26], white matter hyperintensities [27], lifestyle-related disease (hypertension, type II diabetes mellitus, and lipid abnormality) [28], high plasma C-reactive protein level [29], orthostatic blood pressure behavior [30], and unstable body mass index [31]. Our study explored the older age, APOE ε4 allele positive and low MMSE score at baseline, but not the gender and education years, were the independent risk predictors to dementia.…”
Section: Discussionmentioning
confidence: 99%